2013
DOI: 10.1080/13557858.2013.814764
|View full text |Cite
|
Sign up to set email alerts
|

Disparate patterns of hospitalisation reflect unmet needs and persistent ethnic inequalities in mental health care: the Scottish health and ethnicity linkage study

Abstract: Our data show disparate patterns of psychiatric hospitalisations by ethnic group in Scotland providing new observations concerning the mental health care experience of Chinese, Mixed background and White subgroups not fully explained by socioeconomic indicators. For South Asian and Chinese groups in particular, our data indicate under and late utilisation of mental health services. These data call for monitoring and review of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…From overlapping papers, Selten et al (2001) was selected instead of Veling et al (2006) and Kirkbride et al (2008) instead of Coid et al (2008). f Eight studies that reported an effect size adjusted for age and sex, as well as an effect size adjusted for age, sex and SES (Selten, 2001;Leao et al, 2006;Weiser et al, 2008;Kirkbride et al, 2008;Bansal et al, 2014;Hollander et al, 2016;Manhica et al, 2016;Kirkbride et al, 2017aKirkbride et al, , 2017b plus two studies that reported an effect size adjusted for age, sex and SES (Barghadouch et al, 2016;Markkula et al, 2017). g Derived from the above eight studies that reported an effect size adjusted for age and sex, and an effect size adjusted for age, sex and SES.…”
Section: Discussionmentioning
confidence: 99%
“…From overlapping papers, Selten et al (2001) was selected instead of Veling et al (2006) and Kirkbride et al (2008) instead of Coid et al (2008). f Eight studies that reported an effect size adjusted for age and sex, as well as an effect size adjusted for age, sex and SES (Selten, 2001;Leao et al, 2006;Weiser et al, 2008;Kirkbride et al, 2008;Bansal et al, 2014;Hollander et al, 2016;Manhica et al, 2016;Kirkbride et al, 2017aKirkbride et al, , 2017b plus two studies that reported an effect size adjusted for age, sex and SES (Barghadouch et al, 2016;Markkula et al, 2017). g Derived from the above eight studies that reported an effect size adjusted for age and sex, and an effect size adjusted for age, sex and SES.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, there is additionally long-standing evidence to suggest that psychiatrists diagnose potential symptoms of mental illness differently depending on the ethnicity of the patient (Bansal et al, 2014;Weich et al, 2014), and perceptions of the SA population as a homogeneous group have been criticised for ignoring the demographic variability and intragroup diversity of the population and giving rise to cultural stereotypes (Burr, 2002). These stereotypes, which are said to stem from a belief that South Asian culture is patriarchal, repressive and inferior to Western culture, have the potential to misdirect diagnosis and also influence standards of care and treatment pathways (Burr, 2002), acting as a further barrier to accessing services.…”
Section: Help-seekingmentioning
confidence: 99%
“…Concerns about mental healthcare inequalities for British BME populations are tangled up with discussions about whether these populations are inappropriately over-represented, for example in terms of psychiatric hospitalisation, or whether rates of mental illness are really higher. Two recent studies (Bansal et al, 2014;Weich et al, 2014), the latter of which had a sample of 1.2 million patients, found higher rates of psychiatric hospitalisation for South Asians than for White people and concluded that these findings evidenced race-based inequality in treatment. However, there is also significant research which points to higher levels of psychological distress in the British South Asian population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Further, migrants have been found to have higher hospitalisation rates and disproportionately high involuntary hospitalisation rates relative to their Anglo‐Australian counterparts (Bansal et al . , Stolk et al . ).…”
Section: Discussionmentioning
confidence: 95%